Plasma concentrations of endogenous heparinoids in portal hypertension. - McKee, R F (1992)
Bleeding as a complication of liver disease can occur in the absence of recognised haemostatic defects. It is now possible to measure the concentration of endogenous heparinoid substances in the blood using a competitive binding assay. One such substance, heparan sulphate (normal range < 600 ng/ml) was assayed in the plasma of 49 patients admitted because of oesophageal varices. In 27 patients with recent upper gastrointestinal bleeding the median plasma heparan sulphate value was 1700 ng/ml (interquartile (IQ) range 900-3900) compared with 390 ng/ml (IQ range 256-800) in 22 patients with no recent bleed (p < 0.01). As heparan sulphate is metabolised by the same route as exogenous heparin, an attempt to establish a cause for the raised heparan concentrations was made by measuring the clearance of exogenous heparin in 10 portal hypertensive patients and 10 controls. The median half life of heparin in plasma in the portal hypertensive patients (25.5 minutes; IQ range 22-34) was significantly longer (p < 0.007) than the median half life in the controls (18.7 minutes; IQ range 17-21.5). Thus, there is evidence of raised concentrations of endogenous heparin like substances in portal hypertensive patients after gastrointestinal bleeding. These high concentrations may result from reduced hepatic clearance.